Spiritual learning communities: historical, systematic and practical observations1 - Roebben, Bert (Revista Pistis & Praxis, 2014)
Children and young people have the inalienable right to be part of a learning community. Nobody can learn on his/her own. Education is always a communal enterprise. In this paper the concept of the ‘spiritual learning community’ is developed as a contemporary answer to the socio-educational issues raised by Martin Buber and John Dewey in the 1930s. Cultural and religious diversity today stimulate education and schooling more than ever before to reconsider the narrative-communicative and spiritual dimension of every learning process. The spiritual dimension of the learning community relates to a specific habitus, namely of de-centration from the self and dedication to the other, and to a specific focus, namely on existential questions such as content of the learning process. Insights from philosophy of education and from European religious education theory and concrete experiences of teacher education at the universities of Dortmund (Germany) and Wien (Austria) form the horizon for this reflection.